Introducing elements of active learning in a small course - Mancinska, Laura (Improving University Science Teaching and Learning, 2023)
Despite the modern consensus that traditional-style lectures do not promote deep and longlasting learning outcomes, many mathematics courses are delivered precisely in this manner.1 How does one incorporate elements of active learning in a pre-established course with traditional-style lectures? Are these additional activities introduced at the expense of covering less material and do more advanced students suffer from this style of teaching? If so, do the advantages outweigh the negative effects in the context of a master’s level mathematics course?